Accelerating discovery of next-generation power electronics materials via high-throughput ab initio screening - Jiashu Chen; Mingzhu Liu; Minghui Liu; Xinzhong Wang; Yiwen Su; Guangping Zheng (npj Computational Materials)
Abstract Power electronics (PEs) play a pivotal role in electrical energy conversion and regulation for applications spanning from consumer devices to industrial infrastructure. Wide-bandgap (WBG) semiconductors such as SiC, GaN, and Ga2O3 have emerged as high-performance materials in PEs. Nevertheless, the WBG materials have some limitations that there exists the proliferation of intrinsic defects, with prohibitively high fabrication costs. We identify next-generation PEs materials beyond SiC, GaN, and Ga2O3 based on a high-throughput computational methodology. A massive database affording 153,235 materials is screened by leveraging ab initio methods with the thorough evaluation of bandgap, electron mobility, thermal conductivity, and Baliga and Johnson figures of merit (BFOM and JFOM). The comprehensive and effective theoretical analysis identifies some promising candidates (B2O3, BeO, and BN) that possess high BFOM, JFOM, and lattice thermal conductivity. Our methodology could be extended to other application domains of electronics, simplifying the process of exploring new materials.